Determinants of Iron Deficiency Anemia in a Cohort of Children Aged 6-71 Months Living in the Northeast of Minas Gerais, Brazil. - Francisca Helena Calheiros Zanin; Camilo Adalton Mariano da Silva; Élido Bonomo; Romero Alves Teixeira; Cíntia Aparecida de Jesus Pereira; Karina Benatti dos Santos; Maria Arlene Fausto; Deborah Aparecida Negrão-Correa; Joel Alves Lamounier; Mariângela Carneiro (PLoS ONE, 2015)
Iron deficiency anemia is one of the most common nutritional disorders worldwide. The aim was to identify the prevalence and incidence of anemia in children and to identify predictors of this condition, including intestinal parasites, social, nutritional and environmental factors, and comorbidities. A population-based cohort study was conducted in a sample of 414 children aged 6-71 months living in Novo Cruzeiro in the Minas Gerais State. Data were collected in 2008 and 2009 by interview and included socio-economic and demographic information about the children and their families. Blood samples were collected for testing of hemoglobin, ferritin and C-reactive protein. Anthropometric measurements and parasitological analyses of fecal samples were performed. To identify risk factors associated with anemia multivariate analyses were performed using the generalized estimating equations (GEE). In 2008 and 2009, respectively, the prevalence rates of anemia were 35.9% (95%CI 31.2-40.8) and 9.8% (95%CI 7.2-12.9), the prevalence rates of iron deficiency were 18.4% (95%CI 14.7-22.6) and 21.8% (95%CI 17.8-26.2), and the incidence rates of anemia and iron deficiency were 3.2% and 21.8%. The following risk factors associated with anemia were: iron deficiency (OR = 3.2; 95%CI 2.0-.5.3), parasitic infections (OR = 1.9; 95%CI 1.2-2.8), being of risk of or being a low length/height-for-age (OR = 2.1; 95%CI 1.4-3.2), and lower retinol intake (OR = 1.7; 95%CI 1.1-2.7), adjusted over time. Nutritional factors, parasitic infections and chronic malnutrition were identified as risk factors for anemia. These factors can be verified in a chronic process and have been classically described as risk factors for these conditions.